Resisting the pressures of globalisation: The repeated failure of elite sport reforms in re-united Germany - Meier, H. E.; García, B.; Konjer, M. (German Politics, 2021)
During the German divide, the two Germanys developed quite different elite sport systems. After reunification, the expensive and compromised East German state sport system was dismantled and the West German neo-corporatist policy approach to elite sport prevailed. The neo-corporatist approach is characterised by a large number of veto players which constantly bargain over influence and scarce resources. Globalisation and the diffusion of East German policy approaches have increased the competitive intensity in international sport and made the neo-corporatist approach increasingly anachronistic. Declining competitiveness has inspired several initiatives of the federal government to reform elite sport policymaking. So far, German elite sport seems to represent a policy domain where neo-corporatism resists the pressures of globalisation.